An observational study on the effect of seasonal variation on peritoneal dialysis patients - Yu, Zanzhe; Ding, Li; He, Yanna; Huang, Jiaying; Fang, Wei; Gu, Leyi; Ni, Zhaohui; Wang, Qin (Frontiers in Physiology, 2023)
Background: Seasonal variation has impact on plants, wild animals and also human beings. Data has shown seasonal variation has significant impact on patient fluid status, biochemistry results and outcomes in hemodialysis population. The relevant data on peritoneal dialysis was scant. Methods: It was a cross sectional study. All patients followed up in the center had peritoneal equilibration test and PD adequacy test every 6 months. All peritoneal equilibration test and PD adequacy test data were collected during Dec 2019 to Nov 2020. The monthly delivery information of the whole center was collected from 2015 to 2019. Results: There were 366 patients and 604 sets of peritoneal equilibration test and PD adequacy test results in the study. Plasma albumin and phosphate levels were higher in summer. Monthly average outdoor temperature was positively correlated to plasma albumin. There was no seasonal difference in peritoneal dialysis ultrafiltration or urine volume. The percentage of low glucose concentration (1.5%) usage was higher in summer and lower in winter. Conclusion: Plasma albumin and phosphate levels were higher in summer in PD patients. Less strong glucose peritoneal dialysis dialysate was more widely used in summer. Understanding the seasonal variation of peritoneal dialysis is helpful in individualized treatment.